2023
DOI: 10.3390/ijms24032809
|View full text |Cite
|
Sign up to set email alerts
|

Interfering with the Ubiquitin-Mediated Regulation of Akt as a Strategy for Cancer Treatment

Abstract: The serine/threonine kinase Akt modulates the functions of numerous substrates, many of them being involved in cell proliferation and growth, metabolism, angiogenesis, resistance to hypoxia and migration. Akt is frequently deregulated in many types of human cancers, its overexpression or abnormal activation being associated with the increased proliferation and survival of cancer cells. A promising avenue for turning off the functionality of Akt is to either interfere with the K63-linked ubiquitination that is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 147 publications
0
8
0
Order By: Relevance
“…Furthermore, in combination with RNA-seq we found that indole oligomers could inhibit MM cell proliferation by suppressing AKT phosphorylation. AKT activation and degradation are known to be involved in various biological responses, such as cell survival, proliferation, protein translation, and metabolism ( 33 35 ). Many oncogenes and proto-oncogenes are protein kinases that undergo phosphorylation, and their activation often contributes to tumorigenesis ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in combination with RNA-seq we found that indole oligomers could inhibit MM cell proliferation by suppressing AKT phosphorylation. AKT activation and degradation are known to be involved in various biological responses, such as cell survival, proliferation, protein translation, and metabolism ( 33 35 ). Many oncogenes and proto-oncogenes are protein kinases that undergo phosphorylation, and their activation often contributes to tumorigenesis ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…AKT exists in three highly homologous isoforms that can be ubiquitinated by different E3 ligases. Depending on the type of ubiquitination, this may result in the activation of the pathway, via K63 ubiquitination, or its inhibition via K48 ubiquitination [ 42 ]. Among all the AKT-activating E3 ligases, two are overexpressed in osteosarcoma.…”
Section: Ubiquitinationmentioning
confidence: 99%
“…As a proto-oncogene, Akt plays a crucial role in various biological processes. Disruptions to the Akt signaling pathway are associated with multiple human diseases, such as cancer, cardiovascular disease, and neurological disorders [ 24 , 25 ]. And it’s reported that phosphorylated Akt could upregulate the expression of nuclear factor E2-related factor 2 (Nrf2), which was involved in antioxidant and cytoprotective functions, inhibition of inflammation, and modulation of microglial functional phenotype [ 26 29 ].…”
Section: Introductionmentioning
confidence: 99%